Peran Pemerintah Gampong dalam Meningkatkan Kegiatan Keagamaan di Gampong Doy, Banda Aceh - Turiza, Maysyurah; Maysa, Saifullah (Jurnal Riset dan Pengabdian Masyarakat, 2021)
The gampong government is a group of people the community has trusted because of their abilities and good backgrounds. In this case, the role of the gampong government is closely related to fostering religious activities. Because it is used as a guide for religious activities in the community, we want to know what roles the village government plays in fostering religious activities. The existence of religious activities is fundamental in human life, especially during a pandemic recently. This study uses a qualitative method that aims to find out the kind of activities in the village Ie Masen. This study found that teaching and learning tajwÄ«d and reading Al-Quran activities are fully supported by the gampong Doy Banda Aceh government.